Case Report of blaNDM-7-Harboring IncX3 Plasmid in ST196 Klebsiella quasipneumoniae in China - Sun L; Li G; Meng N; Wang Z; Wang H; Wang J; Jiao X (Infection and Drug Resistance, 2022)
Lin Sun,1,2,* Guiling Li,3,4,* Nan Meng,1 Zhenyu Wang,1 Hanyun Wang,1 Jing Wang,1,2 Xinan Jiao1,2 1Jiangsu Key Laboratory of Zoonosis/Jiangsu Co-Innovation Center for Prevention and Control of Important Animal Infectious Diseases and Zoonoses, Yangzhou University, Yangzhou, Jiangsu, People’s Republic of China; 2Key Laboratory of Prevention and Control of Biological Hazard Factors (Animal Origin) for Agrifood Safety and Quality, Ministry of Agriculture of China, Yangzhou University, Yangzhou, Jiangsu, People’s Republic of China; 3Department of Laboratory Medicine, Clinical Medical College, Yangzhou University, Yangzhou, Jiangsu, People’s Republic of China; 4Clinical Testing Center, Northern Jiangsu People’s Hospital, Yangzhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Wang; Xinan Jiao, Email wj1231@yzu.edu.cn; jiao@yzu.edu.cnAbstract: Klebsiella quasipneumoniae isolate SBH035 was recovered from a patient in Jiangsu Province, China. The isolate showed resistance to ampicillin, cefazolin, cefotaxime, meropenem, ceftazidime–avibactam, and fosfomycin. The carbapenemase-encoding gene blaNDM-7 was identified, and whole genome sequencing analysis indicated that blaNDM-7 was located in an IncX3 plasmid with a conserved structure of IS 26-ΔcutA-tat-trpF-bleMBL-blaNDM-7-ISAba125-IS 3000-ΔTn2. To date, this is the first identification of a blaNDM-7-harboring IncX3 plasmid in ST196 K. quasipneumoniae from a patient in China. Greater attention to controlling the dissemination of IncX3 plasmids is needed owing to potential horizontal transfer via mobile genetic elements.Keywords: Klebsiella quasipneumoniae, ST196, carbapenem resistance, blaNDM-7, IncX3 plasmid